Detection and functional portrayal of a novel class of dihydrotestosterone derived selective progesterone receptor modulators (SPRM). Issue 147 (March 2015) - Andrieu, Thomas; Mani, Orlando; Goepfert, Christine; Bertolini, Reto; Guettinger, Andreas; Setoud, Raschid; Uh, Kayla Y.; Baker, Michael E.; Frey, Felix J.; Frey, Brigitte M.
Graphical abstract: Highlights: Screening of DHT-derivatives with antiprogestin activity. Antiprogestin activity assessed using binding, QPCR and reporter assays. Antiprogestins and breast cancer cell lines proliferation. 3D modeling of DHT-derivative with progesterone receptor. Abstract: In early pregnancy, abortion can be induced by blocking the actions of progesterone receptors (PR). However, the PR antagonist, mifepristone (RU38486), is rather unselective in clinical use because it also cross-reacts with other nuclear receptors. Since the ligand-binding domain of human progesterone receptor (hPR) and androgen receptor (hAR) share 54% identity, we hypothesized that derivatives of dihydrotestosterone (DHT), the cognate ligand for hAR, might also regulate the hPR. Compounds designed and synthesized in our laboratory were investigated for their affinities for hPRB, hAR, glucocorticoid receptor (hGRα) and mineralocorticoid receptor (hMR), using whole cell receptor competitive binding assays. Agonistic and antagonistic activities were characterized by reporter assays. Nuclear translocation was monitored using cherry-hPRB and GFP–hAR chimeric receptors. Cytostatic properties and apoptosis were tested on breast cancer cells (MCF7, T-47D). One compound presented a favorable profile with an apparent neutral hPRB antagonistic function, a selective cherry-hPRB nuclear translocation and a cytostatic effect. 3D models of human PR and AR with this ligand were constructed to investigate the molecular basis of selectivity. Our data suggest that these novel DHT-derivatives provide suitable templates for the development of new selective steroidal hPR antagonists.